(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Forming and maintaining a healthy lifestyle is the main guarantee of general health and well-being. A healthy lifestyle includes a set of habits and practices that promote physical, mental, and emotional well-being. By making healthy lifestyle choices, people can increase their quality of life, reduce their risk of chronic disease, and improve overall health outcomes. This article provides information about the health guarantee of a healthy lifestyle.